ACCESS TO HOUSING FOR MIGRANT SINGLE MOTHERS - Greta Skubiejūtė, (PEOPLE: International Journal of Social Sciences, 2025)
This study explores migrant single mothers’ access to housing and its crucial role in family reunification, wellbeing, and social integration. The analysis combines a comparative review of housing policies in three destination countries representing different welfare regimes—the United Kingdom, Germany, and Norway—with 30 semi-structured interviews conducted with Lithuanian single mothers who migrated to these countries. The findings reveal that, in formal terms, migrant single mothers enjoy similar access to housing as nationals (in the case of the UK, prior to Brexit). Nevertheless, they encounter a range of additional barriers, including limited awareness of their eligibility for housing support, language difficulties, discrimination in the rental market, and constraints associated with employer-provided accommodation in remote areas, which restrict independent housing searches. Despite these challenges, access to adequate housing emerges as a fundamental condition for migrant single mothers, particularly as it determines their ability to bring their children to live with them in the host country. Housing also represents their largest financial burden, and securing stable, affordable accommodation significantly reduces stress and economic vulnerability. Furthermore, living in quality housing in well-connected neighbourhoods—as opposed to marginalised or low-income social housing areas—enhances both mothers’ and children’s quality of life by ensuring access to essential services, education, and opportunities for social integration. The study highlights housing as not merely a material need but a cornerstone of social inclusion and family stability for migrant single mothers in Europe.